Greenhouse gas fluxes from agricultural soils of Kenya and Tanzania - Rosenstock, Todd S.; Mpanda, Mathew; Pelster, David E.; Butterbach-Bahl, Klaus; Rufino, Mariana C.; Thiong'o, Margaret; Mutuo, Paul; Abwanda, Sheila; Rioux, Janie; Kimaro, Anthony A.; Neufeldt, Henry (Wiley, 2016)
Knowledge of greenhouse gas (GHG) fluxes in soils is a prerequisite to constrain national, continental, and global GHG budgets. However, data characterizing fluxes from agricultural soils of Africa are markedly limited. We measured carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4) fluxes at 10 farmer‐managed sites of six crop types for 1 year in Kenya and Tanzania using static chambers and gas chromatography. Cumulative emissions ranged between 3.5–15.9 Mg CO2‐C ha−1 yr−1, 0.4–3.9 kg N2O‐N ha−1 yr−1, and −1.2–10.1 kg CH4‐C ha−1 yr−1, depending on crop type, environmental conditions, and management. Manure inputs increased CO2 (p = 0.03), but not N2O or CH4, emissions. Soil cultivation had no discernable effect on emissions of any of the three gases. Fluxes of CO2 and N2O were 54–208% greater (p < 0.05) during the wet versus the dry seasons for some, but not all, crop types. The heterogeneity and seasonality of fluxes suggest that the available data describing soil fluxes in Africa, based on measurements of limited duration of only a few crop types and agroecological zones, are inadequate to use as a basis for estimating the impact of agricultural soils on GHG budgets. A targeted effort to understand the magnitude and mechanisms underlying African agricultural soil fluxes is necessary to accurately estimate the influence of this source on the global climate system and for determining mitigation strategies.